Assessing Knowledge, Attitudes, and Practices: Regarding Hepatitis B Infection and Vaccination Among Healthcare Professionals at AL-Salama Hospital, Ameria, Baghdad City: A Cross-Sectional Investigation Conducted in October-November 2022. - Atshan, Fawzi Hashim; Al-Khayyat, Basil Abdullrazzaq Saadallah; Ghali, Ehab Jumaa; Alsherees, Hashim (Medical Science Journal for Advance Research, 2023)
Hepatitis B Virus (HBV): A High-Risk Infection for Healthcare Workers (HCWs) , Healthcare workers (HCWs) are at an increased risk of contracting the highly dangerous hepatitis B virus (HBV) due to their frequent exposure to contaminated bodily fluids, particularly blood. Implementing precautionary measures such as personal safety protocols and vaccination can effectively prevent HBV infection. Objective: 1- Evaluation of Healthcare Professionals’ Knowledge, Attitudes, and Practices (KAP) Regarding Hepatitis B Infection and Vaccination. 2- Evaluating Immunization Status of Healthcare Workers (HCWs) in Al-Salama-Ameria Hospital, Primary Care, and Specialist Dental Care Centers in Relation to Hepatitis B Virus (HBV). Materials and methods: In October and November 2022, a cross-sectional study was conducted at Al Salama Hospital (90 participants), primary care centers (44 participants), and specialist dental care centers (20 participants) in Ameria, Baghdad. A self-administered, structured questionnaire was used to collect information, including the knowledge, attitudes, and practices (KAP) of healthcare workers (HCWs) as well as their demographic details. The study data were analyzed using descriptive statistics, including frequencies, proportions, and percentages, with the assistance of Excel software. Verbal consent was obtained from each participant, and their identities were kept anonymous throughout the study. Results: Our research comprised a total of 154 healthcare workers (HCWs), consisting of 59 A medical facility comprised of 95 medical staff and 95 paramedical staff, possessing a collective wealth of knowledge. score among the participants was 68%, indicating a moderate level of knowledge. In terms of attitude, the overall score was 75%, indicating a positive attitude towards hepatitis B virus (HBV) infection and vaccination. However, the overall practice score was 58%, indicating a need for improvement in implementing preventive measures. Within the medical staff, a mere 15% had undergone HBV screening, while a significant 67% had successfully received the recommended three doses of vaccination. among the paramedical staff who had not been previously screened for HBV, only 37% had completed the three doses of vaccination. Conclusion: The findings of the study indicated that healthcare workers (HCWs) had a higher overall attitude score (75%) compared to their knowledge (68%) and practice (58%) scores. However, the rate of vaccination, particularly among paramedical staff, was low.